A novel metal-organic framework aerogel based hydrated salt composite phase change material for enhanced solar thermal utilization. (February 2023) - Hu, Tao; Wu, Ziheng; Fang, Yaobing; Niu, Junyi; Yuan, Wenhui; Li, Li
Abstract: In recent years, metal-organic frameworks (MOFs) have been regarded as ideal carriers for phase change materials (PCMs) due to their outstanding properties and attractive structures. In this work, a novel shape-stabilized SAT/Fe-EA aerogel composite PCM is prepared by impregnating sodium acetate trihydrate (SAT) into MOF aerogel with iron as the metal ion and ellagic acid (EA) as the organic ligand. The three-dimensional network structure of Fe-EA aerogel and Fe-EA guarantee sufficient supporting space, excellent light-to-thermal effect and efficient heat transfer rate, leading to an ultra-high heat storage density (245.6 J/g) and excellent light-to-thermal conversion performance (the light-to-thermal conversion efficiency is up to 94.5 %). Besides, benefit from the abundant pore structure and hydrophilic surface of Fe-EA aerogel obtained via freeze-drying, which could provide a large number of heterogeneous nucleation sites for SAT, the supercooling degree of SAT is decreased to as low as 2.07–2.63 °C. Notably, the supercooling degree shows no significant change after 200 cycles, and the SAT/Fe-EA aerogel composite PCM still maintains a high heat storage density of 214.9 J/g, exhibiting a superior thermal reliability. Consequently, the SAT/Fe-EA aerogel composite PCM could be a promising candidate for solar thermal storage systems. Graphical abstract: Unlabelled Image Highlights: Fe-EA aerogel shows good hydrophilic properties. The composite PCM exhibits low supercooling degree. The existence of Fe-EA aerogel reinforces the light-to-thermal conversion. This work provides a new strategy for improving solar thermal utilization.